GAMBARAN FAKTOR RESIKO TERJADINYA KANKER PAYUDARA DI RUMAH SAKIT UMUM PUSAT HAJI ADAM MALIK MEDAN - Simatupang, Melva; Samsider Sitorus; Indah Risky (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
In 2022, breast cancer will be the first most common cancer in the world with 2.3 million cases (11.7%). The incidence of breast cancer has increased by 1% from 2 million cases of breast cancer in 2020 to 2.3 million cases in 2022. The number of new cases of breast cancer was 68,858 cases (16.6%) out of a total of 396,914 new cases of cancer in Indonesia. With the number of deaths reaching more than 22.4 thousand cases, when compared with the death rate in 2020, there will be a decrease in the death rate due to breast cancer by around 1.4% in 2022 from 22.6 thousand deaths in 2020 to 22.4 thousand deaths in 2022. to determine the risk factors for breast cancer at Haji Adam Malik General Hospital, Medan in 2024. This research was a descriptive study with a cross-sectional design. Samples were taken using a simple random sampling technique and 86 respondents were obtained. The results of the study showed that the risk factors for breast cancer were the majority of age (> 50 years), 39 sufferers (68.4%), 36 sufferers (78.3%) at menarche < 12 years old, 42 sufferers (76.4%) had a history of using hormonal contraceptives (76.4%). family history of 37 sufferers (68.5%), parity of not having children as many as 22 sufferers (68.8%). Midwives are expected to be able to provide early breast cancer screening, both self-breast examination and clinical breast examination, especially those who have a family history of breast cancer.